PERAN KOMITMEN ORGANISASIONAL DALAM MEMEDIASI PENGARUH KEPUASAN KERJA TERHADAP TURNOVER INTENTION AGEN PT PRUDENTIAL INDONESIA LIFE ASSURANCE DENPASAR - Mahendra, I Komang Gede; Sudibya, I Gde Adnyana; Dewi, I. G. A. Manuati (Buletin Studi Ekonomi, 2017)
This study aims to explain the effect of job satisfaction and organizational commitment to turnover intention and role of organizational commitment in mediating the effect of job satisfaction on turnover intention. The research population is all unit manager at Prudential 4 Denpasar branch office in Denpasar and use 167 samples with probability sampling method. To determine the number of samples, used Slovin formula. Methods of data collection using survey methods with questionnaires as a tool. Data were analyzed using Partial Least Squares analysis. The results of the study found that job satisfaction has a significant effect on turnover intention. Organizational commitment was also found to have a significant effect on turnover intention. Furthermore, organizational commitment was found to mediate the effect of job satisfaction on turnover intention. The implication of this research is, in order to suppress the emergence of intention turnover, top managers of Prudential Indonesia need to maintain employee loyalty, especially the unit manager, to the company. The management of Prudential Indonesia also needs to maintain the suitability of existing work practices in the field with the expectation of employees, especially the unit manager, then keep the work situation to be conducive, so as not to cause excessive pressure. Keywords: job satisfaction, organizational commitment, turnover intention